Prevalence of invasive Trichosporonosis by Trichosporon asahii and other Trichosporon species and their antifungal susceptibility pattern in Chhattisgarh - Pradhan, Sagarika; Agrawal, Ekta; Murthy, Ramanesh; Tomar, Rashmi (International Journal of Medical Research and Review, 2017)
Introduction: Trichosporonosis is usually known to cause superficial mycoses, but now it is emerged as an opportunistic infectious disease. Trichosporon species is fairly uncommon fungus but can cause fatal mycosis in immunocompromised patients. Objective: This study is an attempt to know prevalence of invasive trichosporonosis and its antifungal susceptibility. Materials and Methods: All patients with a culture that was positive for Trichosporon species from February 2012 to February 2015 were included. Routine mycology works up done and suspected Trichosporon sp. were confirmed by automated miniAPI system. Antifungal susceptibility test was done for Fluconazole (F), Itraconazole(Itr), Voriconazole(V), Flucytosine(5Fc), AmphotericinB (AMB) done by minimum inhibitory concentration (MIC) method by ATB Fungus3 ( Biomerieux, France). Result: 41 Trichosporon sp. was isolated from clinical specimen. Trichosporon asahii was the most common isolate (29 out of 41, 70.7%), followed by T. mucoides (5 of 41, 12.2%), T. inkin (2 of 41, 4.9%) and other Trichosporon sp. (5 out of 41,12.2%). Out of 41, 20 cases were proven to cause invasive trichosporonosis. Most invasive infections were associated with indwelling catheter (95%), associated bacterial infection(85%), ICU stay (85% each), prior antibiotic use (75%), cancer (65%), neutropenia, steroid use (55% each) and chemotherapy(50%). Amphotericin B was less susceptible against Trichosporon isolates whereas azole had good in vitro activity. Sensitivity of T.asahii towards Fluconazole, Itraconazole, Voriconazole, Amphotericin B and Flucytosine was 72.4%, 51.7%, 86.2%, 51.7% and 66.8% respectively. Conclusion: T. asahii and other unusual Trichosporon sp.species also cause invasive trichosporonosis. For optimal therapy for trichosporonosis azoles can play a potential role.